Developments in offshore engineering : wave phenomena and offshore topics - Herbich, John B.; Ansari, Khyruddin A. (Gulf Pub. Co., 1999)
Drawing from experts and top researchers from around the world, this book presents current developments in a variety of areas that impact offshore and ocean engineering.